Invertebrates and restoration: Interview with Jonathan Majer - Majer, Jonathan; McDonald, Tein (Wiley-Blackwell Publishing Ltd, 2013)
Entomologist Jonathan Majer is a world pioneer in using ants as indicators of restoration success. With hundreds of published works to his name (and five species of ants named after him), he reflects in this interview on his undimming passion for learning and teaching about invertebrates - a group of animals that can include up to 95% of faunal species in a reference community.